Retardation film, retardation film set, or manufacturing method of lens part or display system

Efficient weight reduction and visibility improvements are achieved by integrating the retardation film with λ/4 members in a specific optical path and integrating it with the lens portion with a curved main surface.

JP2025044444APending Publication Date: 2025-04-02NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023152011
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing VR goggles have challenges in weight reduction and field of view improvement, especially in display systems using thin lenses.

Method used

Using a manufacturing method, an optical film with specific phase difference characteristics is formed by integrating the retardation film with a λ/4 member in a specific optical path. The film has a flat phase difference of 100 nm to 190 nm and a phase difference change rate of 0.07 or less and is integrated with the lens portion with a curved main surface.

Benefits of technology

The weight reduction of VR goggles is achieved while improving the visibility of the display system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044444000001_ABST
    Figure 2025044444000001_ABST
Patent Text Reader

Abstract

To provide a retardation film capable of favorably achieving weight saving of a VR goggle while improving visibility, a retardation film set, or a manufacturing method of a lens part or a display system.SOLUTION: A display system 10 includes a display element 12; a reflection type polarization member 14 configured to reflect light emitted from the display element 12; a first lens part 16 having a curved surface and arranged on an optical path between the display element 12 and the reflection type polarization member 14; a half mirror 18 arranged between the display element 12 and the first lens part 16; a first λ / 4 member 20 arranged on an optical path between the display element 12 and the half mirror 18; and a second λ / 4 member 22 arranged on an optical path between the half mirror 18 and the reflection type polarization member 14. A manufacturing method includes integrating a retardation film having an in-plane phase difference Re of 100 nm to 190 nm and an absolute value of a phase difference change value RS of 0.07 or less, as the second λ / 4 member 22, with the first lens part 16.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a retardation film, a retardation film set, or a lens portion or a display system. [Background technology]

[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices), are rapidly becoming widespread. In image display devices, optical members such as polarizing members and phase difference members are generally used to realize image display and to improve the performance of the image display (see, for example, Patent Document 1).

[0003] In recent years, new applications for image display devices have been developed. For example, goggles with displays (VR goggles) for realizing Virtual Reality (VR) have begun to be commercialized. Since VR goggles are being considered for use in various situations, there is a demand for them to be lightweight and have improved visibility. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2021-103286 A Summary of the Invention [Problem to be solved by the invention]

[0005] The weight of the VR goggles can be reduced by, for example, thinning the lenses used in the VR goggles. On the other hand, there is a demand for the development of optical members suitable for display systems using thin lenses.

[0006] In view of the above, the main object of the present invention is to provide a retardation film, a retardation film set, or a manufacturing method for a lens portion or a display system that can effectively achieve weight reduction of VR goggles while improving visibility. [Means for solving the problem]

[0007] [1] According to one aspect of the present invention, there is provided a method for manufacturing a display system for displaying an image to a user, the display system including: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member arranged in front of the display element and reflecting the light emitted from the display element; a first lens unit arranged on an optical path between the display element and the reflective polarizing member and having a curved main surface; a half mirror arranged between the display element and the first lens unit, transmitting the light emitted from the display element and reflecting the light reflected by the reflective polarizing member toward the reflective polarizing member; the retardation film has an in-plane retardation Re(550) of 100 nm to 190 nm and an absolute value of a retardation change value RS per unit thickness of 0.07 or less (wherein the retardation change value RS is the gradient of an approximation line of the in-plane retardation Re(550) of the retardation film measured under conditions of applying tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg), and the second λ / 4 member is integrated with the first lens portion. [2] The manufacturing method described in [1] above may include preparing two of the retardation films, integrating one of the retardation films with the display element as the first λ / 4 member, and integrating the other of the retardation films with the first lens portion as the second λ / 4 member. [3] According to another aspect of the present invention, there is provided a method for manufacturing a lens unit used in a display system for displaying an image to a user, the lens unit including: a reflective polarizing member that reflects light that is emitted forward from a display surface of a display element that displays an image and that has passed through a polarizing member and a first λ / 4 member; a first lens unit that is disposed on an optical path between the display element and the reflective polarizing member and has a curved main surface; and a half-mirror that is disposed between the display element and the first lens unit, transmits light emitted from the display element, and reflects light reflected by the reflective polarizing member toward the reflective polarizing member. and a second λ / 4 member disposed on an optical path between the half mirror and the reflective polarizing member, the second λ / 4 member being a retardation film having an in-plane retardation Re(550) of 100 nm to 190 nm and an absolute value of a retardation change value RS per unit thickness of 0.07 or less (wherein the retardation change value RS is the gradient of an approximation line of the in-plane retardation Re(550) of the retardation film measured under conditions of applying tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg). [4] According to yet another aspect of the present invention, there is provided a retardation film having an in-plane retardation Re(550) of 100 nm to 190 nm, an absolute value of a retardation change value RS per unit thickness of 0.07 or less, and the retardation change value RS being a gradient of an approximation line of the in-plane retardation Re(550) of the retardation film measured under tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg. [5] In the retardation film according to the above item [4], the in-plane retardations Re(450), Re(550), and Re(650) may satisfy the following relationships (i) to (iii): (i) 100 nm <Re(550)<160nm、 (ii) Re(450) / Re(550)<1; (iii) Re(650) / Re(550)>1. [6] The retardation film according to the above [4] or [5] may have a dimensional change rate of 0.02% or less before and after a heat treatment at 85° C. for 500 hours. [7] In the retardation film according to any one of the above [4] to [6], the absolute value of the difference in in-plane retardation Re(550) before and after heat treatment at 85° C. for 500 hours may be 3.5 nm or less. [8] The retardation film according to any one of the above [4] to [7] may be a stretched resin film. [9] In the retardation film according to any one of the above [4] to [8], the resin film may contain a polycarbonate-based resin.

[10] The retardation film according to any one of the above items [4] to [9] may be integrated with a member having a curved surface.

[11] The curved surface of the member to which the retardation film according to the above item

[10] is integrated may have a radius of curvature of 20 mm or more.

[12] The retardation film according to any one of [4] to

[11] above may have a difference of 0.06 or less between the ellipticity of transmitted light having a wavelength of 550 nm when linearly polarized light whose polarization direction forms an angle of 45° with respect to the slow axis is incident on the center of the retardation film when the retardation film is integrated with a member having a curved surface with a radius of curvature of 75 mm and the ellipticity before integration.

[13] The retardation film according to any one of [4] to

[12] above may be used as the second λ / 4 member by being integrated with the first lens unit in a display system including: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member arranged in front of the display element and reflecting the light emitted from the display element; a first lens unit having a curved main surface that is arranged on an optical path between the display element and the reflective polarizing member; a half mirror arranged between the display element and the first lens unit that transmits the light emitted from the display element and reflects the light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member arranged on the optical path between the display element and the half mirror; and a second λ / 4 member arranged on the optical path between the half mirror and the reflective polarizing member.

[14] According to another aspect of the present invention, there is provided a display system comprising: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member arranged in front of the display element and reflecting the light emitted from the display element; a first lens section arranged on an optical path between the display element and the reflective polarizing member and having a curved main surface; a half mirror arranged between the display element and the first lens section, transmitting the light emitted from the display element and reflecting the light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member arranged on the optical path between the display element and the half mirror; and a second λ / 4 member arranged on the optical path between the half mirror and the reflective polarizing member, wherein the second λ / 4 member and the first lens section are integrated. and a set of a first retardation film for constituting the first λ / 4 member and a second retardation film for constituting the second λ / 4 member, wherein the first retardation film and the second retardation film each have an in-plane retardation Re(550) of 100 nm to 190 nm and an absolute value of a retardation change value RS per unit thickness of 0.07 or less (wherein the retardation change value RS is the slope of an approximation line of the in-plane retardation Re(550) of the retardation film measured under conditions of applying tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg), and the absolute value of the difference between the in-plane retardation Re(550) of the first retardation film and the in-plane retardation Re(550) of the second retardation film is 5 nm or less. Effect of the Invention

[0008] According to the retardation film, the retardation film set, or the method for manufacturing the lens portion or the display system according to the embodiment of the present invention, it is possible to effectively achieve a reduction in the weight of the VR goggles while improving the visibility. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an example of a method for integrating a retardation film with a member having a curved surface. [Diagram 2] FIG. 1A is a schematic cross-sectional view illustrating a method for measuring the ellipticity of a retardation film integrated with a member having a curved surface, and FIG. 1B is a schematic view of the state of FIG. 1A as viewed from the retardation film side. [Diagram 3] FIG. 1 is a schematic diagram showing a general configuration of an example of a display system for VR goggles. [Figure 4] FIG. 2 is a schematic cross-sectional view illustrating a configuration of an example of an integrated product of a retardation film and a member having a curved surface, and a partially enlarged cross-sectional view thereof. [Diagram 5] FIG. 2 is a schematic cross-sectional view illustrating a configuration of an example of an optical laminate including a retardation film. [Figure 6] FIG. 13 is a diagram for explaining a method for measuring the variation in thickness. [Figure 7] FIG. 1 is a diagram for explaining a method for measuring an ISC value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described with reference to the drawings, but the present invention is not limited to these embodiments. In order to clarify the description, the drawings may be schematic in terms of the width, thickness, shape, etc. of each part compared to the embodiment, but they are merely examples and do not limit the interpretation of the present invention. In addition, in the drawings, the same or equivalent elements are given the same reference numerals, and duplicate descriptions may be omitted.

[0011] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.

[0012] A. Retardation film According to one aspect of the present invention, there is provided a retardation film in which the absolute value of the retardation change value RS per unit thickness (unit: μm) is 0.07 or less. The retardation film can be suitably used in a state integrated with a member having a curved surface. The retardation change value "RS" is the slope of the approximate straight line of the in-plane retardation Re(550) of the retardation film measured under the application of tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg, and can be an index of the degree of change in the in-plane retardation when a tension is applied to the retardation film. Specifically, a small absolute value of RS means that the in-plane retardation hardly changes when a tension is applied to the retardation film. When integrated with a member having a curved surface, a tension is applied to the retardation film, and as a result, the retardation may change. However, if the absolute value of RS per unit thickness is within the above range, the retardation change can be suppressed. Also, dimensional changes and retardation changes due to heating can be suppressed. The absolute value of RS per unit thickness may be, for example, 0.06 or less or 0.05 or less, and may be, for example, 0.005 or more. Also, the absolute value of RS of the retardation film may be, for example, 0.005 to 5.00, or for example, 0.10 to 4.00.

[0013] The retardation film preferably exhibits a refractive index characteristic of nx > ny ≧ nz. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within a range that does not impair the effects of the present invention, ny < nz may occur. The Nz coefficient of the retardation film is preferably 0.9 to 3, more preferably 0.9 to 2.5, still more preferably 0.9 to 1.5, and particularly preferably 0.9 to 1.3.

[0014] The in-plane retardation Re(550) of the retardation film is, for example, 100 nm to 190 nm, may be 110 nm to 180 nm, may be 130 nm to 160 nm, or may be 135 nm to 155 nm. In one embodiment, the retardation film satisfies the relationship of 100 nm < Re(550) < 160 nm.

[0015] The retardation film preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. Re(450) / Re(550) of the retardation film is, for example, less than 1, and may be 0.95 or less, or may be less than 0.90, or may be 0.85 or less. Re(450) / Re(550) of the retardation film is, for example, 0.75 or more. Re(650) / Re(550) of the retardation film may be, for example, more than 1, more than 1 and 1.2 or less, or may be 1.01 to 1.15. A retardation film exhibiting an inverse dispersion wavelength characteristic can contribute to improving visibility when applied to a display system such as VR goggles.

[0016] When linearly polarized light, the polarization direction of which forms an angle of 45° with respect to the slow axis, is incident on the retardation film from the normal direction, the ellipticity of transmitted light having a wavelength of 550 nm measured at a polar angle of 0° (normal direction) is, for example, 0.80 or more, preferably 0.85 or more, and more preferably 0.90 to 1. The ellipticity is the ratio of the minor axis / major axis of circularly polarized light, and for example, the ellipticity of completely circularly polarized light is 1, and the ellipticity of completely linearly polarized light is 0. A retardation film exhibiting the above ellipticity can contribute to improved visibility when applied to a display system such as VR goggles.

[0017] The dimensional change rate ((dimension before heat treatment-dimension after heat treatment) / dimension before heat treatment×100) of the retardation film before and after heat treatment at 85° C. for 500 hours is, for example, 0.02% or less, and may be 0.015% or less, or 0.01% or less. A retardation film exhibiting the above dimensional change rate has the advantage that peeling due to heating is unlikely to occur when used as a laminate with other members.

[0018] The difference in in-plane retardation Re(550) before and after the heat treatment when the retardation film is subjected to heat treatment at 85° C. for 500 hours (|Re(550) before heat treatment−Re(550) after heat treatment|) is, for example, 3.5 nm or less, and may be 3.3 nm or less, or 3 nm or less. When the retardation film exhibits the above-mentioned difference in in-plane retardation, a decrease in visibility due to heating can be suppressed when the retardation film is applied to a display system such as VR goggles.

[0019] The ISC value of the retardation film is, for example, 50 or less, preferably 40 or less, more preferably 30 or less, and further preferably 20 or less. The ISC value can be an index of smoothness or unevenness. A retardation film that satisfies such an ISC value and satisfies the absolute value of RS per unit thickness can suppress the occurrence of retardation unevenness when integrated with a member having a curved surface.

[0020] The thickness variation of the retardation film is preferably 1 μm or less, more preferably 0.8 μm or less, further preferably 0.6 μm or less, and even more preferably 0.4 μm or less. With such thickness variation, for example, the ISC value can be satisfactorily achieved. Here, the thickness variation can be obtained by measuring the thickness of a first portion located in the plane of the retardation film and the thickness of a position spaced a predetermined distance (for example, 5 mm to 15 mm) from the first portion in any direction (for example, upward, downward, leftward, and rightward) from the first portion.

[0021] The ISC value per unit thickness of the retardation film is preferably not more than 1, more preferably not more than 0.7, and further preferably not more than 0.5. The ISC value per unit thickness can be determined, for example, by dividing the ISC value by the thickness (unit: μm).

[0022] As described above, the retardation film can be used in a state where it is integrated with a member having a curved surface. More specifically, the retardation film can be used in a state where it is integrated with the curved surface of a member having a curved surface. The curved surface may be a concave surface or a convex surface. The radius of curvature of the curved surface is, for example, 20 mm or more, for example, 25 mm or more, or for example, 30 mm or more, and is, for example, 150 mm or less, preferably 125 mm or less, more preferably 110 mm or less, and may be 90 mm or less. The diameter (major axis) of the member having a curved surface can be, for example, 20 mm to 80 mm, or for example, 30 mm to 70 mm. A preferable example of the member having a curved surface is a lens having a concave surface.

[0023] The retardation film and the member having a curved surface can be integrated by any appropriate method. FIG. 1 is a schematic diagram for explaining an example of a method for integrating a retardation film and a member having a curved surface. In FIG. 1(a), the retardation film 1 is arranged on the member L, which is an adherend, in the state of the retardation film 3 with the adhesive layer 2 provided on one side thereof. The member L is circular in plan view and has a concave shape on the top in cross-sectional view. The retardation film 3 with the adhesive layer can be arranged at a predetermined position by chucking its end to a fixing jig (not shown). The retardation film 3 with the adhesive layer is arranged at a position where the adhesive layer 2 contacts the edge of the concave surface of the member L, and is pressed into the concave surface side using a jig or the like in a state softened by heating, so that it is bonded over the entire concave surface of the member L as shown in FIG. 1(b). Thereafter, as shown in FIG. 1(c), unnecessary parts of the retardation film 3 with the adhesive layer (for example, parts protruding from the member L in plan view) are removed to obtain an integrated product.

[0024] In the integration with the curved surface, typically, the retardation film may be stretched. For example, the retardation film may be stretched from a planar shape (circular shape) corresponding to the planar shape of the member L to a curved shape along the curved shape of the member L. In this way, tension may be applied to the retardation film in the integration with the curved surface, and since the absolute value of RS per unit thickness of the retardation film is small, a change in retardation due to the application of tension may be suppressed.

[0025] As shown in Fig. 2, the retardation film 1 is circular with a radius of 32.5 mm when viewed from the concave side, and is integrated with a member L having a concave curvature radius of 75 mm, and linearly polarized light whose polarization direction forms an angle of 45° with respect to its slow axis is incident from the convex side in the normal direction to the center C of the member L (in other words, the center 1c of the retardation film 1). The difference between the ellipticity of transmitted light with a wavelength of 550 nm measured on the concave side in the normal direction and the ellipticity in the portion corresponding to the center 1c of the retardation film 1 before integration (ellipticity before integration - ellipticity after integration) is, for example, 0.06 or less, preferably 0.05 or less, more preferably 0 to 0.04. Such a retardation film can contribute to improving display characteristics when used in a display system in a state where it is integrated with a member having a curved surface.

[0026] 2, when the retardation film 1 is integrated with the member L, the difference between Re(550) at the center 1c of the curved retardation film 1 after integration and Re(550) at a portion of the retardation film corresponding to the center 1c before integration (|Re(550) before integration-Re(550) after integration|) is, for example, 6 nm or less, preferably 5 nm or less, and more preferably 4 nm or less. Such a retardation film can contribute to improving display characteristics when used in a display system in a state where it is integrated with a member having a curved surface.

[0027] As shown in FIG. 2, when the retardation film 1 is integrated with the member L, the maximum absolute value of the difference between Re(550) at the center 1c of the retardation film 1 and Re(550) at the other portion (outer portion) may be, for example, 30 nm or less, 25 nm or less, or 20 nm or less, and may be, for example, 1 nm or more. When stretched during integration with the member L, the in-plane retardation may vary within the plane (curved surface) of the retardation film. For example, in a curved retardation film after integration, the Re(550) of a portion far from the center may have a large difference from the Re(550) of the center. According to the retardation film having the absolute value of RS per unit thickness, even when stretched during integration with the member L, the variation in the in-plane retardation within the plane can be reduced.

[0028] The retardation film is made of any appropriate material that can satisfy the above characteristics. The retardation film may be, for example, a stretched resin film or an oriented and solidified layer of a liquid crystal compound.

[0029] Examples of the resin contained in the resin film include polycarbonate-based resins, polyester carbonate-based resins, polyester-based resins, polyvinyl acetal-based resins, polyarylate-based resins, cycloolefin-based resins, cellulose-based resins, polyvinyl alcohol-based resins, polyamide-based resins, polyimide-based resins, polyether-based resins, polystyrene-based resins, and acrylic-based resins. These resins may be used alone or in combination (for example, blends or copolymers). When the retardation film exhibits reverse dispersion wavelength characteristics, a resin film containing a polycarbonate-based resin or a polyester carbonate-based resin (hereinafter, sometimes simply referred to as a polycarbonate-based resin) can be suitably used.

[0030] As the polycarbonate-based resin, any suitable polycarbonate-based resin can be used as long as the effects of the present invention can be obtained. For example, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from at least one dihydroxy compound selected from the group consisting of an alicyclic diol, an alicyclic dimethanol, a di-, tri- or polyethylene glycol, and an alkylene glycol or a spiro glycol. Preferably, the polycarbonate-based resin contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, a structural unit derived from an alicyclic dimethanol, and / or a structural unit derived from a di-, tri- or polyethylene glycol; more preferably, it contains a structural unit derived from a fluorene-based dihydroxy compound, a structural unit derived from an isosorbide-based dihydroxy compound, and a structural unit derived from a di-, tri- or polyethylene glycol. The polycarbonate-based resin may contain a structural unit derived from another dihydroxy compound as necessary. Details of polycarbonate-based resins that can be suitably used for retardation films and methods for forming retardation films are described in, for example, JP-A-2014-10291, JP-A-2014-26266, JP-A-2015-212816, JP-A-2015-212817, and JP-A-2015-212818, and the descriptions in these publications are incorporated herein by reference.

[0031] When the retardation film is a stretched resin film, the thickness is, for example, 20 μm to 150 μm, preferably 30 μm to 100 μm, more preferably 35 μm to 80 μm, and further preferably 40 μm to 70 μm.

[0032] The above-mentioned liquid crystal compound alignment solidified layer is a layer in which the liquid crystal compound is aligned in a predetermined direction within the layer, and the alignment state is fixed. The "alignment solidified layer" is a concept that includes an alignment solidified layer obtained by hardening a liquid crystal monomer as described later. Typically, rod-shaped liquid crystal compounds are aligned in the slow axis direction of the retardation film (homogeneous alignment). Examples of rod-shaped liquid crystal compounds include liquid crystal polymers and liquid crystal monomers. The liquid crystal compound is preferably polymerizable. If the liquid crystal compound is polymerizable, the alignment state of the liquid crystal compound can be fixed by aligning the liquid crystal compound and then polymerizing it.

[0033] The alignment solidified layer of the liquid crystal compound (liquid crystal alignment solidified layer) can be formed by performing an alignment treatment on the surface of a predetermined substrate, applying a coating liquid containing a liquid crystal compound to the surface to align the liquid crystal compound in a direction corresponding to the alignment treatment, and fixing the alignment state. Any appropriate alignment treatment can be adopted as the alignment treatment. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be mentioned. Specific examples of mechanical alignment treatment include rubbing treatment and stretching treatment. Specific examples of physical alignment treatment include magnetic field alignment treatment and electric field alignment treatment. Specific examples of chemical alignment treatment include oblique deposition method and photoalignment treatment. As the treatment conditions of various alignment treatments, any appropriate conditions can be adopted depending on the purpose.

[0034] The alignment of the liquid crystal compound is performed by treating the liquid crystal compound at a temperature at which the liquid crystal compound exhibits a liquid crystal phase according to the type of liquid crystal compound. By performing such temperature treatment, the liquid crystal compound takes on a liquid crystal state and is aligned according to the alignment treatment direction of the substrate surface.

[0035] In one embodiment, the alignment state is fixed by cooling the liquid crystal compound aligned as described above. When the liquid crystal compound is polymerizable or crosslinkable, the alignment state is fixed by subjecting the liquid crystal compound aligned as described above to a polymerization treatment or crosslinking treatment.

[0036] As the liquid crystal compound, any suitable liquid crystal polymer and / or liquid crystal monomer is used. The liquid crystal polymer and the liquid crystal monomer may be used alone or in combination. Specific examples of the liquid crystal compound and the method for producing the liquid crystal alignment solidified layer are described in, for example, JP 2006-163343 A, JP 2006-178389 A, and WO 2018 / 123551 A. The descriptions in these publications are incorporated herein by reference.

[0037] When the retardation film is a layer in which a liquid crystal compound is aligned and solidified, the thickness is, for example, 1 μm to 10 μm, preferably 1 μm to 8 μm, more preferably 1 μm to 6 μm, and further preferably 1 μm to 4 μm.

[0038] In the manufacture of the retardation film, the RS per unit thickness of the retardation film obtained can be changed by changing the forming material, manufacturing conditions, etc. For example, in a retardation film which is a stretched film of a resin film, the absolute value of RS per unit thickness tends to become smaller by reducing the stretching ratio, etc. In addition, in the case of a resin film containing a polycarbonate-based resin, the absolute value of RS per unit thickness tends to become smaller by increasing the content ratio of the structural unit derived from a fluorene-based dihydroxy compound. On the other hand, a retardation film which is a liquid crystal alignment solidified layer can have a very small absolute value of RS per unit thickness.

[0039] B. Display System FIG. 3 is a schematic diagram showing the general configuration of a display system according to one embodiment of the present invention, and shows the arrangement and shape of each component of the display system. The display system 10 includes a display element 12, a reflective polarizing member 14, a first lens unit 16 having a curved main surface, a half mirror 18, a first λ / 4 member 20, a second λ / 4 member 22, and a second lens unit 24. The reflective polarizing member 14 is disposed in front of the display surface 12a of the display element 12, and can reflect light emitted from the display element 12. The first lens unit 16 is disposed on the optical path between the display element 12 and the reflective polarizing member 14, and the half mirror 18 is disposed between the display element 12 and the first lens unit 16. The first λ / 4 member 20 is disposed on the optical path between the display element 12 and the half mirror 18, and the second λ / 4 member 22 is disposed on the optical path between the half mirror 18 and the reflective polarizing member 14. Although not shown, from the viewpoint of improving visibility, the display system 10 may further include an absorptive polarizing member. The absorptive polarizing member may be disposed in front of the reflective polarizing member such that the reflection axis of the reflective polarizing member 14 and the absorption axis of the absorptive polarizing member are approximately parallel to each other.

[0040] The half mirror, or the components arranged forward from the first lens portion (in the illustrated example, the half mirror 18, the first lens portion 16, the second λ / 4 member 22, the reflective polarizing member 14, and the second lens portion 24) may be collectively referred to as the lens portion (lens portion 4).

[0041] The display element 12 is, for example, a liquid crystal display or an organic EL display, and has a display surface 12a for displaying an image. The light emitted from the display surface 12a passes through, for example, a polarizing member that may be included in the display element 12, and is converted into a first linearly polarized light.

[0042] The first λ / 4 member 20 can convert the first linearly polarized light incident on the first λ / 4 member 20 into the first circularly polarized light. The first λ / 4 member 20 may be provided integrally with the display element 12.

[0043] The half mirror 18 transmits the light emitted from the display element 12 and reflects the light reflected by the reflective polarizing member 14 toward the reflective polarizing member 14. The half mirror 18 is provided integrally with the first lens portion 16.

[0044] The second λ / 4 member 22 can transmit the light reflected by the reflective polarizing member 14 and the half mirror 18 through the reflective polarizing member 14. The second λ / 4 member 22 is provided integrally with the first lens portion 16.

[0045] The first circularly polarized light output from the first λ / 4 member 20 passes through the half mirror 18 and the first lens portion 16, and is converted into the second linearly polarized light by the second λ / 4 member 22. The second linearly polarized light output from the second λ / 4 member 22 is reflected toward the half mirror 18 without passing through the reflective polarizing member 14. At this time, the polarization direction of the second linearly polarized light incident on the reflective polarizing member 14 is the same as the reflection axis of the reflective polarizing member 14. Therefore, the second linearly polarized light incident on the reflective polarizing member 14 is reflected by the reflective polarizing member 14.

[0046] The second linearly polarized light reflected by the reflective polarizing member 14 is converted into the second circularly polarized light by the second λ / 4 member 22, and the second circularly polarized light emitted from the second λ / 4 member 22 passes through the first lens unit 16 and is reflected by the half mirror 18. The second circularly polarized light reflected by the half mirror 18 passes through the first lens unit 16 and is converted into the third linearly polarized light by the second λ / 4 member 22. The third linearly polarized light passes through the reflective polarizing member 14. At this time, the polarization direction of the third linearly polarized light incident on the reflective polarizing member 14 is the same as the transmission axis of the reflective polarizing member 14. Therefore, the third linearly polarized light incident on the reflective polarizing member 14 passes through the reflective polarizing member 14.

[0047] The light transmitted through the reflective polarizing member 14 passes through the second lens portion 24 (the absorptive polarizing member 28 and the second lens portion 24) and enters the eye 26 of the user.

[0048] The absorption axis of the polarizing member included in the display element 12 and the reflection axis of the reflective polarizing member 14 may be disposed approximately parallel to each other or approximately perpendicular to each other. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the first λ / 4 member 20 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°. The angle between the absorption axis of the polarizing member included in the display element 12 and the slow axis of the second λ / 4 member 22 is, for example, 40° to 50°, may be 42° to 48°, or may be about 45°.

[0049] The in-plane retardation Re(550) of the first λ / 4 member 20 is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The first λ / 4 member 20 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the first λ / 4 member 20 may be, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less.

[0050] The in-plane retardation Re(550) of the second λ / 4 member 22 is, for example, 100 nm to 190 nm, and may be 110 nm to 180 nm, 130 nm to 160 nm, or 135 nm to 155 nm. The second λ / 4 member 22 preferably exhibits an inverse dispersion wavelength characteristic in which the retardation value increases according to the wavelength of the measurement light. The Re(450) / Re(550) of the second λ / 4 member 22 may be, for example, 0.75 or more and less than 1, or 0.8 or more and 0.95 or less. The in-plane retardation of the second λ / 4 member is, unless otherwise specified, an in-plane retardation measured at a portion corresponding to the center of the first lens portion. The center of the first lens portion may be a portion that is generally recognized as the center. For example, the center of the first lens portion may be the center of a circumscribing circle of its planar shape.

[0051] In the display system 10, the second λ / 4 member 22 is composed of the retardation film described in Section A, and is integrated with the first lens unit 16 having a curved surface. The integration of the second λ / 4 member 22 and the first lens unit 16 can be performed by integrating the above-mentioned retardation film as the second λ / 4 member 22 with the first lens unit. The second λ / 4 member (the retardation film described in Section A) 22 can be integrated with the first lens unit 16 as an optical laminate that optionally further includes other optical members and has an adhesive layer (for example, a pressure-sensitive adhesive layer) on the outermost layer, for example.

[0052] The radius of curvature of the curved surface of the first lens portion 16 is, for example, 20 mm or more, for example, 25 mm or more, or for example, 30 mm or more, and may be, for example, 150 mm or less, preferably 125 mm or less, more preferably 110 mm or less, or may be 90 mm or less. The diameter (major axis) of the first lens portion 16 may be, for example, 20 mm to 80 mm, or for example, 30 mm to 70 mm. In the illustrated example, the second λ / 4 member 22 is integrated with the concave surface of the first lens portion 16, but may be integrated with the convex surface. The method of integrating the second λ / 4 member or the optical laminate with the first lens portion is not particularly limited, and for example, the same method as the method of integrating the retardation film with the member having a curved surface described in section A can be used.

[0053] FIG. 4 is a schematic cross-sectional view and an enlarged view of a main part of an integrated product 100 in which an optical laminate 70 including a second λ / 4 member (a retardation film described in Section A) 22 and a first lens unit 16 are integrated. The optical laminate 70 includes a member (a so-called second positive C plate) 72 whose refractive index characteristics can show the relationship nz>nx=ny, which is arranged on one side of the second λ / 4 member 22, and a second protective member 74 arranged on the other side. The second λ / 4 member 22, the second positive C plate 72, and the second protective member 74 are typically laminated via an adhesive layer (adhesive layer, pressure-sensitive adhesive layer, etc.). The optical laminate 70 further includes a second adhesive layer 76 on the side of the second positive C plate 72 opposite to the side on which the second λ / 4 member 22 is arranged. The optical laminate 70 is bonded to the first lens unit 16 by the second adhesive layer 76 so as to follow the concave surface 16a of the first lens unit 16.

[0054] The thickness direction retardation Rth(550) of the second positive C plate is preferably -20nm to -200nm, more preferably -30nm to -180nm, further preferably -40nm to -160nm, and particularly preferably -50nm to -140nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. The in-plane retardation Re(550) of the second positive C plate is, for example, less than 10nm.

[0055] The second positive C plate may be formed of any suitable material, but is preferably composed of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of such liquid crystal compounds and methods for forming the second positive C plate include the liquid crystal compounds and methods for forming the retardation layer described in

[0020] to

[0028] of JP-A-2002-333642. In this case, the thickness of the second positive C plate is preferably 0.5 μm to 5 μm.

[0056] The second protective member typically includes a substrate. The substrate may be made of any appropriate film. Examples of materials that are the main components of the film that constitutes the substrate include cellulose-based resins such as triacetyl cellulose (TAC), polyester-based, polyvinyl alcohol-based, polycarbonate-based, polyamide-based, polyimide-based, polyethersulfone-based, polysulfone-based, polystyrene-based, cycloolefin-based such as polynorbornene, polyolefin-based, (meth)acrylic-based, acetate-based, and other resins. The thickness of the substrate is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and even more preferably 15 μm to 35 μm.

[0057] The second protective member preferably has a substrate and a surface treatment layer formed on the substrate. The second protective member having the surface treatment layer may be disposed so that the surface treatment layer is located on the front side. The surface treatment layer may have any appropriate function. For example, from the viewpoint of improving visibility, the surface treatment layer preferably has an anti-reflection function. The surface treatment layer may also include a hard coat layer. The thickness of the surface treatment layer is preferably 1 μm to 20 μm, more preferably 2 μm to 15 μm, and further preferably 3 μm to 10 μm.

[0058] The adhesive constituting the second adhesive layer typically contains a (meth)acrylic polymer, a urethane polymer, a silicone polymer, or a rubber polymer as a base polymer. Preferably, the adhesive is a (meth)acrylic adhesive containing a (meth)acrylic polymer as a main component. The thickness of the second adhesive layer is, for example, 12 μm or more, preferably 15 μm or more, and, for example, 100 μm or less, preferably 80 μm or less.

[0059] In the display system 10, the first λ / 4 member 20 may also be composed of the retardation film described in Section A. In this case, the first λ / 4 member (the retardation film described in Section A) 20 may be integrated with the display surface 12a of the display element 12. The display surface of the display element may be flat. As described above, the retardation film described in Section A has a small absolute value of RS per unit thickness, and the change in optical properties due to integration with a member having a curved surface is small. Therefore, when the retardation film described in Section A is integrated along the display surface of the display element, which is flat, and the curved surface of the first lens portion, which has a curved surface, as the first λ / 4 member and the second λ / 4 member, respectively, a display system in which the difference in in-plane retardation between the two is small can be suitably obtained. In such a display system, the absolute value of the difference between the in-plane retardation Re(550) of the retardation film (first λ / 4 member) integrated with the display element and the in-plane retardation Re(550) of the retardation film (second λ / 4 member) integrated with the first lens portion is, for example, 6 nm or less, preferably 5 nm or less, more preferably 4 nm or less, and even more preferably 3.5 nm or less, and may be, for example, 3.0 nm or less, 2.5 nm or less, 2.0 nm or less, 1.5 nm or less, or 1.0 nm or less.

[0060] The first λ / 4 member (the retardation film described in Section A) 20 may, for example, further include any other appropriate optical members and be integrated with the display element 12 as an optical laminate having an adhesive layer (e.g., a pressure-sensitive adhesive layer) on the outermost layer.

[0061] FIG. 5 is a schematic cross-sectional view for explaining an example of the configuration of an optical laminate 80 including a first λ / 4 member (a retardation film described in Section A) 20. The optical laminate 80 includes a polarizing member 82 arranged on one side of the first λ / 4 member 20, and a first positive C plate 84 and a first protective member 86 arranged in this order on the other side. The polarizing member 82 is a polarizing member that can be included in the display element 12. The optical laminate 80 further includes a first adhesive layer 88 on the side of the polarizing member 82 opposite to the side on which the first λ / 4 member 20 is arranged. The optical laminate 80 can be attached to the front side of the display element by the first adhesive layer 88.

[0062] The polarizing member is typically an absorptive polarizing member, and may include a resin film containing a dichroic material (sometimes referred to as an absorptive polarizing film). The thickness of the absorptive polarizing film is, for example, 1 μm or more and 20 μm or less, and may be 2 μm or more and 15 μm or less, 12 μm or less, 10 μm or less, 8 μm or less, or 5 μm or less.

[0063] The absorptive polarizing film may be prepared from a single layer of resin film, or may be prepared using a laminate of two or more layers.

[0064] When preparing from a single-layer resin film, for example, an absorptive polarizing film can be obtained by subjecting a hydrophilic polymer film such as a polyvinyl alcohol (PVA)-based film, a partially formalized PVA-based film, or an ethylene-vinyl acetate copolymer-based partially saponified film to a dyeing treatment with a dichroic substance such as iodine or a dichroic dye, a stretching treatment, etc. Among them, an absorptive polarizing film obtained by dyeing a PVA-based film with iodine and uniaxially stretching it is preferable.

[0065] The dyeing with iodine is carried out, for example, by immersing the PVA film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be carried out after the dyeing treatment or while the dyeing is being carried out. Alternatively, the stretching may be followed by dyeing. If necessary, the PVA film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like.

[0066] Examples of the laminate produced using the laminate of two or more layers include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The absorptive polarizing film obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced, for example, by coating a PVA-based resin solution on the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into an absorptive polarizing film. In this embodiment, preferably, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction, thereby shrinking the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of PVA, and to achieve high optical properties. At the same time, by increasing the orientation of PVA in advance, problems such as a decrease in the orientation or dissolution of PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the disorder of the orientation of polyvinyl alcohol molecules and the decrease in the orientation can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of the absorptive polarizing film obtained through treatment steps in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction through drying shrinkage treatment.The obtained laminate of resin substrate / absorptive polarizing film may be used as it is (i.e., the resin substrate may be used as a protective layer for the absorptive polarizing film), or any suitable protective layer may be laminated on the peeled surface of the resin substrate / absorptive polarizing film laminate after peeling the resin substrate from the laminate, or on the surface opposite to the peeled surface, depending on the purpose. Details of the method for producing such an absorptive polarizing film are described in, for example, JP2012-73580A and JP6470455A. The entire disclosures of these publications are incorporated herein by reference.

[0067] The crossed transmittance (Tc) of the absorptive polarizing member (absorptive polarizing film) is preferably 0.5% or less, more preferably 0.1% or less, and even more preferably 0.05% or less. The single transmittance (Ts) of the absorptive polarizing member (absorptive polarizing film) is, for example, 41.0% to 45.0%, and preferably 42.0% or more. The polarization degree (P) of the absorptive polarizing member (absorptive polarizing film) is, for example, 99.0% to 99.997%, and preferably 99.9% or more.

[0068] The crossed transmittance, single transmittance and degree of polarization can be measured, for example, using an ultraviolet-visible spectrophotometer. The degree of polarization P can be calculated from the obtained Tp and Tc by measuring the single transmittance Ts, parallel transmittance Tp and crossed transmittance Tc using an ultraviolet-visible spectrophotometer, using the following formula. Note that Ts, Tp and Tc are Y values ​​measured using a 2-degree visual field (C light source) according to JIS Z 8701 and corrected for visibility. Polarization degree P(%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0069] The same explanations as for the second positive C plate, the second protective member, and the second adhesive layer can be applied to the first positive C plate, the first protective member, and the first adhesive layer, respectively.

[0070] C. Setting the retardation film According to another aspect of the present invention, there is provided a set of two retardation films, each of which has an in-plane retardation Re(550) of 100 nm to 190 nm and an absolute value of a retardation change value RS per unit thickness of 0.07 or less. The absolute value of the difference between the in-plane retardation Re(550) of the two retardation films included in the set is, for example, 10 nm or less, preferably 7 nm or less, more preferably 0 nm to 5 nm. Each of the two retardation films included in the set is preferably the retardation film described in section A.

[0071] As shown in Fig. 3, the display system may include a planar first λ / 4 member and a curved second λ / 4 member. In such a display system, by using one of the retardation films to form the first λ / 4 member and the other to form the second λ / 4 member, even when the other retardation film is deformed to follow the curved surface of the first lens portion, the difference in in-plane retardation between the first λ / 4 member and the second λ / 4 member can be made small (for example, the absolute value of the difference in in-plane retardation Re(550) is 10 nm or less, preferably 7 nm or less, more preferably 5 nm or less, and even more preferably 0 nm to 3.5 nm), and as a result, a display system with excellent visibility can be preferably obtained. EXAMPLES

[0072] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The thickness, orientation function, single transmittance and polarization degree are values ​​measured by the following measurement methods. <Thickness> The thickness of 10 μm or less was measured using a scanning electron microscope (manufactured by JEOL, product name "JSM-7100F"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C"). <Phase difference> The in-plane retardation at 23° C. was measured using a birefringence mapping measurement device (manufactured by Photoron, product name “KAMAKIRI X stage”).

[0073] [Example 1] Into a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and reflux condensers controlled at 100°C, 42.47 parts by weight (0.066 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by weight (0.200 mol) of isosorbide (ISB), 42.28 parts by weight (0.139 mol) of spiroglycol (SPG), 63.77 parts by weight (0.298 mol) of diphenyl carbonate (DPC), and 1.19 x 10 calcium acetate monohydrate as a catalyst were added. -2 Weight part (6.78×10 -5 mol) was added. After the inside of the reactor was purged with nitrogen under reduced pressure, the reactor was heated with a heat medium, and stirring was started when the inside temperature reached 100°C. 40 minutes after the start of the temperature increase, the inside temperature reached 220°C, and while controlling to maintain this temperature, the pressure was reduced to 13.3kPa in 90 minutes after reaching 220°C. Phenol vapor by-produced with the polymerization reaction was led to a reflux condenser at 100°C, a small amount of monomer components contained in the phenol vapor were returned to the reactor, and uncondensed phenol vapor was led to a condenser at 45°C and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and the oligomerized reaction liquid in the first reactor was transferred to the second reactor. Next, the temperature increase and pressure reduction in the second reactor were started, and the inside temperature was 240°C and the pressure was 0.2kPa in 50 minutes. Thereafter, polymerization was allowed to proceed until the specified stirring power was reached. When the predetermined power was reached, nitrogen was introduced into the reactor to restore pressure, and the produced polyester carbonate resin was extruded into water and the strands were cut to obtain pellets. The obtained polyester carbonate resin (pellets) was vacuum dried at 80°C for 5 hours, and then a long resin film with a thickness of 118 μm was produced using a film-making device equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a chill roll (setting temperature: 120-130°C) and a winder. The obtained long resin film was stretched in the width direction at a stretching temperature of 139° C. and a stretching ratio of 2.5 times, and then wound into a roll to obtain a retardation film 1 having a thickness of 47 μm, a Re(590) of 140 nm, and an Nz coefficient of 1.2. The Re(450) / Re(550) of the retardation film 1 was 0.859, and the retardation film 1 exhibited inverse dispersion wavelength characteristics.

[0074] [Example 2] The amount of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane was 29.60 parts by weight (0.046 mol), a long resin film having a thickness of 120 μm was prepared, and the resin film was stretched in the width direction at a stretching temperature of 137° C. and a stretching ratio of 2.1 times. The same procedure as in Example 1 was followed to obtain a retardation film 2 having a thickness of 57 μm, an Re(590) of 140 nm, and an Nz coefficient of 1.2. The Re(450) / Re(550) of the retardation film 2 was 0.859, and the film showed inverse dispersion wavelength characteristics.

[0075] [Example 3] A long resin film having a thickness of 114 μm was prepared, and the resin film was stretched in the width direction at a stretching temperature of 136° C. and a stretching ratio of 2.0 times. The same procedure as in Example 1 was repeated to obtain a retardation film 3 having a thickness of 57 μm, a Re(590) of 140 nm, and an Nz coefficient of 1.2. The retardation film 3 had a Re(450) / Re(550) of 0.859, and exhibited inverse dispersion wavelength characteristics.

[0076] [Comparative Example 1] The amount of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane was 29.60 parts by weight (0.046 mol), a long resin film having a thickness of 122 μm was produced, and the resin film was stretched in the width direction at a stretching temperature of 143° C. and a stretching ratio of 3.3 times. The same procedure as in Example 1 was followed to obtain a retardation film C1 having a thickness of 37 μm, an Re(590) of 140 nm, and an Nz coefficient of 1.2. The retardation film C1 had an Re(450) / Re(550) of 0.859 and exhibited inverse dispersion wavelength characteristics.

[0077] [Comparative Example 2] A long resin film having a thickness of 115 μm was prepared, and the resin film was stretched in the width direction at a stretching temperature of 142° C. and a stretching ratio of 3.1 times. The same procedure as in Example 1 was followed to obtain a retardation film C2 having a thickness of 37 μm, a Re(590) of 140 nm, and an Nz coefficient of 1.2. The retardation film C2 had an Re(450) / Re(550) of 0.859 and exhibited inverse dispersion wavelength characteristics.

[0078] [Comparative Example 3] The amount of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane was 29.60 parts by weight (0.046 mol), a long resin film with a thickness of 130 μm was produced, and the resin film was stretched in the width direction at a stretching temperature of 140° C. and a stretching ratio of 2.7 times. The same procedure as in Example 1 was followed to obtain a retardation film C3 with a thickness of 47 μm, Re(590) of 140 nm, and Nz coefficient of 1.2. The retardation film C3 had a Re(450) / Re(550) of 0.859 and exhibited inverse dispersion wavelength characteristics.

[0079] <Phase difference change value RS> The retardation films obtained in the examples and comparative examples were attached to an acrylic film (Re(550)≒0 nm) via an acrylic adhesive layer (thickness 5 μm) to obtain a laminate. The obtained laminate was cut into a length of 150 mm and a width of 15 mm so that the slow axis direction of the retardation film was the longitudinal direction, to obtain a sample. The above acrylic film is a film that hardly changes the retardation when the following tension is applied. Tension was applied in the length direction of the obtained sample using a tensiometer (manufactured by MYCARBON, product name "Digital Luggage Scale"). In the stages of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg of tension, the in-plane phase difference (Re(550)) was measured using a phase difference measuring device (manufactured by Axometrics, product name: Axo Scan). Using Excel functions, with tension on the x-axis and Re(550) on the y-axis, the values of Re(550) measured at each tension were plotted to create an approximate straight line, and the slope of the approximate straight line was taken as the phase difference change value RS. Also, the obtained RS was divided by the film thickness (μm) of each phase difference film to calculate the absolute value of RS per unit thickness.

[0080] <Thickness variation> The phase difference films obtained in the examples and comparative examples were cut into a size of 100 mm × 100 mm to serve as measurement samples. As shown in Fig. 6, the thicknesses at a total of five points, namely the center of the measurement sample and four points each 10 mm away from the center in the vertical and horizontal directions, were measured, and the difference between the maximum value and the minimum value was taken as the thickness variation.

[0081] <ISC value> Regarding the phase difference films obtained in the examples and comparative examples, the ISC value was measured using EyeScale-4W manufactured by Eye System Co., Ltd. Specifically, based on the specifications of the measuring device, the in-plane unevenness was calculated as the ISC value in the ISC measurement mode of the 3CCD image sensor. Fig. 7 is a diagram for explaining the method of measuring the ISC value, and is a schematic view of the arrangement of the light source, phase difference film, screen, and CCD camera as seen from above. As shown in Fig. 7, the light source Ls, phase difference film M, and screen S were arranged in this order, and the transmitted image projected onto the screen S was measured by the CCD camera C. The phase difference film M was attached to a non-alkali glass plate (manufactured by Corning, 1737), and the measurement was performed with the glass plate on the light source Ls side. The distance from the light source Ls to the retardation film M in the X-axis direction was 10 to 60 cm. The distance from the light source Ls to the screen S in the X-axis direction was 70 to 130 cm. The distance from the CCD camera C to the retardation film M in the Y-axis direction was 3 to 30 cm. The distance from the CCD camera C to the screen S in the X-axis direction was 70 to 130 cm.

[0082] <Production and evaluation of curved surface integrated products> 1. Preparation of a lens with a phase difference film An acrylic adhesive layer (thickness 15 μm) was provided on one side of the retardation film obtained in the examples and comparative examples, and the retardation film was attached to the concave surface of a lens having a circular shape with a diameter of 65 mm in plan view and a curvature radius of 75 mm, via the adhesive layer. Specifically, as shown in FIG. 1, the retardation film with the adhesive layer was set so that the surface of the adhesive layer was in contact with the edge of the concave side of the lens, and in a softened state by heating to 120° C., it was pressed into the concave side and attached to the concave surface of the lens. In this way, a lens with a retardation film, which is an integrated product of the retardation film and the lens, was obtained.

[0083] 2. Phase difference change Regarding the lens with retardation film obtained in 1, the in-plane retardation of the retardation film at the center, Re(543) a The Re(543) of the part corresponding to the center of the retardation film before lamination was measured. b and Re(543) a Difference with (Re(543) b -Re(543) a The absolute value of the phase difference (P) was calculated as the change in phase difference at the center due to lamination to a curved surface. Note that the phase difference change due to lamination to a curved surface can be evaluated as "poor (×)" if the difference is 6.0 nm or more, and "good (◯)" if the difference is less than 6.0 nm.

[0084] 3. Change in ellipticity Using a Mueller matrix polarimeter (Axometrics, product name "Axoscan"), linearly polarized light was incident from the normal convex side of the lens with phase difference film at 23°C so that it would pass through the center part of the concave surface. The ellipticity of the transmitted light with a wavelength of 550 nm in the normal direction was measured. a The angle between the polarization direction of the linearly polarized light and the slow axis of the retardation film was 45°. The ellipticity of the retardation film before lamination was also measured in the same manner. b Difference from (ellipticity b -Ovality a ) was calculated as the change in ellipticity of the center due to the bonding of curved surfaces.

[0085] 4. Peeling test The lens with the retardation film was placed in an oven at 80° C. and 0% RH, and taken out after 120 hours. The appearance was visually inspected to evaluate whether the retardation film had peeled off.

[0086] <Production and evaluation of flat integrated products> 1. Preparation of glass plate with retardation film The retardation films obtained in the examples and comparative examples were cut into squares of 100 mm x 100 mm size with the slow axis direction and width direction as side directions, and an acrylic adhesive layer (thickness 5 μm) was provided on one side of the square, and the squares were attached to a flat glass plate (thickness 1.1 mm) via the adhesive layer. This resulted in a glass plate with a retardation film, which was an integrated product of the retardation film and the glass plate.

[0087] 2. Dimensional change The glass plate with the retardation film obtained in 1 was placed in an oven at 85°C and 0% RH, and taken out after 500 hours. Next, the dimensions of the retardation film on the glass plate were measured, and the dimensional change rate before and after heating in the slow axis direction [(dimension before heating - dimension after heating) / dimension before heating x 100] was calculated as the dimensional change rate.

[0088] 3. Phase difference change For the glass plate with retardation film obtained in 1, the in-plane retardation Re(543) of the retardation film was measured. The glass plate with retardation film was then placed in an oven at 85°C and 0% RH, and after 500 hours, it was taken out and the in-plane retardation Re(543) of the retardation film was measured. Re(543) of the retardation film before heat treatment b and Re(543) after heat treatment a Difference with (Re(543) b -Re(543) a The absolute value of the difference between the phase difference and the reflection coefficient was calculated as the change in phase difference due to heating. The phase difference change due to heating can be evaluated as follows: a difference of 4.0 nm or more is "poor (×)", a difference of 3.5 nm or less is "good (◯)", and a difference of more than 3.5 nm and less than 4.0 nm is "passable (△)".

[0089] The results are shown in Table 1. [Table 1]

[0090] The retardation film of the embodiment, which has a small absolute value of RS per unit thickness, exhibits small changes in retardation and ellipticity of transmitted light due to lamination with a lens having a curved surface, and is also unlikely to peel off due to heating. When such a retardation film is applied to a display system as an integrated product with a lens having a curved surface, it can exhibit the desired optical properties and contribute to improving visibility.

[0091] The present invention is not limited to the above-described embodiment, and various modifications are possible. For example, the above-described embodiment may be replaced with a configuration that is substantially the same as the configuration shown in the above-described embodiment, a configuration that provides the same effect, or a configuration that can achieve the same purpose. [Industrial Applicability]

[0092] The manufacturing method of the display system according to the embodiment of the present invention can be suitably used for manufacturing a display system such as, for example, VR goggles. [Explanation of symbols]

[0093] 1 Phase contrast film 10 Display System 12 Display element 14 Reflective polarizing element 16 First lens section 18 Half Mirror 20 First λ / 4 member 22 Second λ / 4 member 24 Second lens section

Claims

1. 1. A method for manufacturing a display system for displaying an image to a user, comprising the steps of: The display system comprises: a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member disposed in front of the display element and configured to reflect light emitted from the display element; a first lens portion disposed on an optical path between the display element and the reflective polarizing member, the first lens portion having a curved main surface; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member disposed on an optical path between the display element and the half mirror; a second λ / 4 member disposed on an optical path between the half mirror and the reflective polarizing member; Equipped with a retardation film having an in-plane retardation Re(550) of 100 nm to 190 nm and an absolute value of a retardation change value RS per unit thickness of 0.07 or less (wherein the retardation change value RS is a gradient of an approximation line of the in-plane retardation Re(550) of the retardation film measured under conditions of applying tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg) to the first lens portion as the second λ / 4 member.

2. Preparing two of the retardation films; One of the retardation films is integrated with the display element as the first λ / 4 member; and The other retardation film is integrated with the first lens portion as the second λ / 4 member; The method of claim 1 , comprising:

3. A method for manufacturing a lens portion used in a display system that displays an image to a user, comprising the steps of: The lens portion is a reflective polarizing member that reflects light that is emitted forward from a display surface of a display element that displays an image and that has passed through the polarizing member and the first λ / 4 member; a first lens portion disposed on an optical path between the display element and the reflective polarizing member, the first lens portion having a curved main surface; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting light reflected by the reflective polarizing member toward the reflective polarizing member; a second λ / 4 member disposed on an optical path between the half mirror and the reflective polarizing member; a retardation film having an in-plane retardation Re(550) of 100 nm to 190 nm and an absolute value of a retardation change value RS per unit thickness of 0.07 or less (wherein the retardation change value RS is a gradient of an approximation line of the in-plane retardation Re(550) of the retardation film measured under conditions of applying tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg) to the first lens portion as the second λ / 4 member.

4. The in-plane retardation Re(550) is 100 nm to 190 nm, The absolute value of the phase difference change value RS per unit thickness is 0.07 or less, The retardation change value RS is the slope of an approximation line of the in-plane retardation Re(550) of the retardation film measured under tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg. Phase contrast film.

5. 5. The retardation film according to claim 4, wherein in-plane retardations Re(450), Re(550), and Re(650) satisfy the following relationships (i) to (iii): (i) 100nm<Re(550)<160nm, (ii) Re(450) / Re(550)<1, (iii) Re(650) / Re(550)>1.

6. The retardation film according to claim 4, which has a dimensional change rate of 0.02% or less before and after a heat treatment at 85°C for 500 hours.

7. 5. The retardation film according to claim 4, wherein an absolute value of a difference in in-plane retardation Re(550) before and after a heat treatment at 85° C. for 500 hours is 3.5 nm or less.

8. The retardation film according to claim 4 , which is a stretched resin film.

9. The retardation film according to claim 8 , wherein the resin film contains a polycarbonate-based resin.

10. The retardation film according to claim 4 , which is integrated with a member having a curved surface.

11. The retardation film according to claim 10 , wherein the curved surface has a radius of curvature of 20 mm or more.

12. 5. The retardation film according to claim 4, wherein when the retardation film is integrated with a member having a curved surface with a radius of curvature of 75 mm, a difference between the ellipticity of transmitted light having a wavelength of 550 nm when linearly polarized light whose polarization direction forms an angle of 45° with respect to the slow axis is incident on the center portion and the ellipticity before integration is 0.06 or less.

13. a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member disposed in front of the display element and configured to reflect light emitted from the display element; a first lens portion disposed on an optical path between the display element and the reflective polarizing member, the first lens portion having a curved main surface; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member disposed on an optical path between the display element and the half mirror; a second λ / 4 member disposed on an optical path between the half mirror and the reflective polarizing member; A display system comprising: The retardation film according to claim 4 , wherein the second λ / 4 member is integrated with the first lens portion.

14. a display element having a display surface that emits light representing an image forward via a polarizing member; a reflective polarizing member disposed in front of the display element and configured to reflect light emitted from the display element; a first lens portion disposed on an optical path between the display element and the reflective polarizing member, the first lens portion having a curved main surface; a half mirror disposed between the display element and the first lens portion, the half mirror transmitting light emitted from the display element and reflecting light reflected by the reflective polarizing member toward the reflective polarizing member; a first λ / 4 member disposed on an optical path between the display element and the half mirror; a second λ / 4 member disposed on an optical path between the half mirror and the reflective polarizing member; Equipped with In a display system in which the second λ / 4 member and the first lens unit are integrated, a set of a first retardation film for constituting the first λ / 4 member and a second retardation film for constituting the second λ / 4 member, The first retardation film and the second retardation film each have an in-plane retardation Re(550) of 100 nm to 190 nm, and an absolute value of a retardation change value RS per unit thickness of 0.07 or less (wherein the retardation change value RS is the slope of an approximation line of the in-plane retardation Re(550) of the retardation film measured under tensions of 0 kg, 0.5 kg, 1 kg, 1.5 kg, and 2 kg); The absolute value of the difference between the in-plane retardation Re(550) of the first retardation film and the in-plane retardation Re(550) of the second retardation film is 5 nm or less; A set of phase contrast films.

Citation Information

Patent Citations

  • Laminate for organic el displays and circular polarizing plate used therefor

    JP2021103286A